PENGARUH VALENTINO ROSSI SEBAGAI BRAND AMBASSADOR DALAM IKLAN YAMAHA R15 TERHADAP KEPUTUSAN PEMBELIAN YAMAHA R15 DI KALANGAN YR15CR CHAPTER PEKANBARU - Muhammad Alif Pratama; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Brand Ambassador as a source of advertising or information about the brand and product attributes pleasant, reassuring and attract public attention. One product that uses a motor vehicle Brand Ambassador is a Yamaha YZF-R15. Yamaha YZF-R15merupakan brand of motor vehicles of the type of sport fairing. In marketing their products, Yamaha YZF-R15 using the Brand Ambassador in advertising. Advertising itself into one of the social media that are very popular, so has the coverage is extensive. Therefore, use of Brand Ambassador YZF-R15 products in advertising may cause consumer purchasing decisions on the Pekanbaru YR15CR community.The method used is quantitative eksplanatif using random sampling techniques and the total sample of 113 respondents. Researchers collected data by questionnaire. To find out how much influence between the variables X and Y, researchers used a simple linear regression analysis. Processing test data questionnaire was conducted using SPSS program Windows Version 23.Based on the results of investigation of the influence of Valentino Rossi as a brand ambassador in the ad Yamaha R15 on purchasing decisions Yamaha R15 among YR15CR chapter Pekanbaru it can be seen the influence of brand ambassadors Valentino Rossi is known tcount 5.409 greater when compared with t table of 1.981, with a significance level of 0.000 smaller than α = 0.05. Based on the model table "Sumarry Model" shows that the value of R = 0.457 and coefficient of determination (Rsquare) is equal to 0.209. The figure shows that the influence of variables influence the understanding Valentino Rossi as a brand ambassador in the ad Yamaha R15 Yamaha R15 purchasing decisions among YR15CR Pekanbaru chapter is 20,9%. This shows the influence of the low category. Keyword: Brand Ambassador, Buy Of Interest, Advertising